Metabolite profile and gene expression of the roots of oil palm seedlings treated with Hendersonia GanoEF1 and infected with Ganoderma boninense - Ismail, Muhammad Faiz; Nulit, Rosimah; Seman, Idris Abu; Ibrahim, Mohd Hafiz; Ramli, Nurrashyeda (Springer Nature Switzerland AG, 2021)
Oil palm (Elaeis guineensis) is considered as a golden crop and is also one of the main contributors to the economy of Malaysia. Unfortunately, Basal Stem Root (BSR) disease caused by Ganoderma boninense remains a major obstacle to oil palm cultivation and production. Hendersonia toruloidea (GanoEF1) is a biocontrol agent and also a novel strain isolated from oil palm plantation soil. Here, we use five-month-old oil palm seedlings and study five treatments to control the disease. Sixty-five (65) compounds from different treatments were selected as the main compounds to be tested, including three types of plant sterols. Release of specific compounds could be used to better understand more the mechanism of endophytic fungi and of the biocontrol to successfully control and suppress G. boninense in oil palm. Phytosterols (β-sitosterol, stigmasterol, and campesterol) were expressed at higher levels in infected than in uninfected seedlings. Other methods which could be used as an indicator to detect plant stress associated with the presence of G. boninense is through the determination of total expression of superoxide dismutase (SOD) and catalase (CAT) in oil palm. Few other studies show a good correlation between stress levels, reactive oxygen species (ROS), and level of SOD and CAT in plant. In this study, we confirm that Hendersonia GanoEF1 plays an important role to control and suppress the BSR disease.